Evaluating the disaster response capacity of the Korean citizen corps in rural areas: A System Dynamics–GIS approach - Jaejoon Lee; Moon-Soo Song; Jinsang Hwang; Seok Bum Hong (iScience)
Summary: With the escalation and complexity of disasters, casualties have increased in rural areas. This underscores the need to strengthen the capabilities of the Citizen Corps Active in Disaster (CAIND) as an effective disaster response mechanism in underdeveloped regions. This study quantitatively assessed vulnerabilities relative to CAIND’s capacity and evaluated the effectiveness of improvement measures. A Monte Carlo analysis using system dynamics was conducted under four scenarios: 100% (baseline), 120%, 140%, and 160% intervention. Results were visualized using geographic information systems. In the baseline scenario, average vulnerability was 0.132, decreasing to 0.126, 0.120, and 0.117 in enhanced scenarios. These reductions correspond to improvements of 4.55%, 9.09%, and 11.36%. The findings suggest that enhancing CAIND’s capacity significantly improves disaster response in rural areas. They also highlight the importance of collaboration among policymakers, community leaders, and researchers in developing effective disaster management strategies for vulnerable regions.